Connectionists Approaches to Language Processing and Acquisition - Plunkett, Kim (HERMES - Journal of Language and Communication in Business, 1991)
The degree to which the behaviour of parallel distributed processing (PDP) models approximates children's acquisition of inflectional morphology has recently been highlighted in discussion of the applicability of PDP to the study of human cognition and language. In this paper, an attempt is made to examine many of the limitations of the Rumelhart and McClelland model and adopt an empirical, comparative approach to the analysis of learning....